Some considerations on the trochleoplasty of distal femur - Alejandro Alvarez López; Rodrigo Fuentes Véjar; Sergio Ricardo Soto Carrasco; Yenima de la Caridad García Lorenzo (Centro Provincial de Información de Ciencias Médicas, 2020)
The poor patellofemoral alignment has multiple anatomical causes and one of them is the dysplasia of the distal femur trochlea, reason why its treatment depends on several factors. To deepen in the essential elements of the trochleoplasty technique, an exhaustive literature review was carried out where some aspects of interest were analyzed, that is: most used classification for the trochlear dysplasias, most important imagenologic elements, indications of the surgical technique, contraindications, main modalities of trochleoplasty and surgical approaches. It was concluded that this is a procedure with very specific indications and can be carried out by means of open surgery or arthroscopic way.